Preparation method of wear-resistant and scratch-resistant water-based ink

By using surface modification technology of water-soluble sodium carboxylate polyimide and nano zinc oxide in polyurethane inks, the shortcomings of polyurethane inks in wear and scratch resistance are solved, and significant improvements in mechanical strength and wear and scratch resistance are achieved.

CN119286305BActive Publication Date: 2025-04-01DONGGUAN HAOCAI INK TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411574403.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-01
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing polyurethane inks have shortcomings in wear and scratch resistance, and it is difficult to meet certain high-demand application scenarios.

Method used

Water-soluble sodium carboxylate polyimide and nano zinc oxide are used as filling additives to improve the mechanical strength and wear and scratch resistance of the ink through surface modification technology.

Benefits of technology

It significantly improves the mechanical strength, wear and scratch resistance of the ink, enhances the tensile performance and hardness of the paint film, while reducing mass loss and brightness changes, and improving overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000009911940000021
    Figure GHA0000009911940000021
  • Figure GHA0000009911940000081
    Figure GHA0000009911940000081
Patent Text Reader

Abstract

The present invention relates to the technical field of inks, and discloses a method for preparing a wear-resistant and scratch-resistant water-based ink, wherein the water-based ink comprises 70-77 parts by weight of water-based polyurethane, 0.5-3 parts by weight of water-soluble sodium carboxylate polyimide, 1-4 parts by weight of nano zinc oxide, and 20-27 parts by weight of color paste. The present invention uses water-based polyurethane as an ink binder, and the sodium carboxylate group of the added water-soluble sodium carboxylate polyimide can interact with the surface of nano zinc oxide, thereby realizing the surface coating modification of nano zinc oxide, which is beneficial to improving the dispersibility of nano zinc oxide in water-based ink, reducing agglomeration, and the water-soluble sodium carboxylate polyimide itself has excellent mechanical strength, wear resistance and other properties, and has good water solubility, and can be well dissolved in water-based polyurethane ink. The tensile properties, hardness, wear resistance and scratch resistance of the ink film are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inks, and in particular to a method for preparing a wear-resistant and scratch-resistant water-based ink. Background Art

[0002] Polyurethane ink is composed of polyurethane binder, color paste, filler, additives, etc. It has the advantages of high adhesion, smooth feel, low temperature curing, high transparency, good weather resistance, etc. It has a wide range of applications in silicone rubber products, electronic appliances, packaging and printing, etc. It is of great significance to improve the mechanical strength, wear resistance and scratch resistance of polyurethane ink.

[0003] Nano zinc oxide has a large specific surface area, high strength, good heat resistance, and strong wear resistance. It is widely used in inks, coatings, plastics, rubbers and other products. Modifying the surface of nano zinc oxide and improving its dispersibility are research hotspots. Commonly used dispersants include sodium polyacrylate, stearic acid, sodium hexametaphosphate, etc. Polyimide is a high-performance resin material with high mechanical strength, good wear resistance, and strong high temperature resistance. It is added to polymer materials such as polyurethane, epoxy resin, and nylon 6 to improve the mechanical and heat resistance of the material. The present invention uses water-soluble sodium carboxylate polyimide and nano zinc oxide as filling additives for polyurethane ink to improve the mechanical strength, wear resistance, scratch resistance and other properties of the ink. Summary of the invention

[0004] (I) Technical Problems to be Solved: In view of the deficiencies in the prior art, the present invention provides a water-based ink with wear resistance and scratch resistance.

[0005] (ii) Technical solution: A method for preparing a wear-resistant and scratch-resistant water-based ink, characterized in that the wear-resistant and scratch-resistant water-based ink comprises 70-77 parts by weight of water-based polyurethane, 0.5-3 parts by weight of water-soluble sodium carboxylate polyimide, 1-4 parts by weight of nano zinc oxide, 20-27 parts by weight of color paste, 0.5-1 parts by weight of defoaming agent, 0.6-1.2 parts by weight of leveling agent, and 0.4-0.7 parts by weight of thickener.

[0006] The preparation method of the wear-resistant and scratch-resistant water-based ink is as follows: water and nano zinc oxide are added into a container, stirred and dispersed, then water-soluble sodium carboxylate polyimide is added, stirred for surface modification, then water-based polyurethane, color paste, defoamer, leveling agent, thickener are added, and sheared and dispersed in a shear emulsifier to obtain the wear-resistant and scratch-resistant water-based ink.

[0007] Preferably, the surface modification temperature is 50-70°C and the time is 2-4 hours.

[0008] Preferably, the preparation method of water-soluble sodium carboxylate polyimide is:

[0009] (1) Add acetonitrile, 4,4'-dinitrodiphenylamine in a molar ratio of 1:(1-1.3):(1.4-2), bromoacetic acid, and potassium carbonate to a flask equipped with a condenser reflux tube, heat to 70-80°C, react for 5-8h, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, then add the recrystallized product to water, add reduced iron powder and concentrated hydrochloric acid, heat to 95-100°C, react for 6-10h, add sodium carbonate for neutralization, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, and obtain 4,4'-diaminodiphenylamine acetic acid. The reaction formula is:

[0010]

[0011] (2) Add N,N-dimethylacetamide, 4,4'-diaminodiphenylamine acetic acid, 1,8-diamino-3,6-dioxaoctane, and 4,4'-biphenyl ether dianhydride in a molar ratio of (0.7-0.9):(0.1-0.3):1 into a flask to react, then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction to obtain carboxyl polyimide.

[0012] (3) Add water and carboxyl polyimide into a flask, add sodium hydroxide to adjust the pH of the solution to 10-12, stir and dry to remove water, wash with ethanol, and obtain water-soluble sodium carboxylate polyimide.

[0013] Preferably, the reaction temperature in (2) is 20-30°C and the reaction time is 8-12h.

[0014] Preferably, the moderately hot imidization reaction (2) is carried out at 100° C. for 1 h, 180° C. for 1.5 h, 200° C. for 1.5 h, and 250° C. for 1 h.

[0015] (III) Technical effect: The present invention uses 4,4'-dinitrodiphenylamine and bromoacetic acid as raw materials, and obtains 4,4'-diaminodiphenylamine acetic acid through substitution reaction and nitro reduction, and then polymerizes with 1,8-diamino-3,6-dioxaoctane containing a hydrophilic ether bond and 4,4'-biphenyl ether dianhydride, and neutralizes with sodium hydroxide, thereby introducing a hydrophilic ether bond into the main chain of the polyimide and a hydrophilic sodium carboxylate group into the side chain, thereby obtaining a water-soluble sodium carboxylate polyimide.

[0016] The invention uses water-based polyurethane as an ink binder, and adds nano zinc oxide and water-soluble sodium carboxylate polyimide. During the surface modification process, the sodium carboxylate group of the side chain of the polyimide can interact with the surface of the nano zinc oxide, thereby realizing the surface coating modification of the nano zinc oxide, which is beneficial to improving the dispersibility of the nano zinc oxide in the water-based ink, reducing agglomeration, and making the nano zinc oxide uniformly dispersed in the water-based polyurethane ink, which is beneficial to improving the mechanical, wear-resistant, and scratch-resistant properties of the ink.

[0017] The water-soluble sodium carboxylate polyimide of the present invention has excellent mechanical strength, wear resistance and other properties, and has good water solubility, and can be well dissolved in water-based polyurethane ink. The uniformly dispersed nano zinc oxide and water-soluble sodium carboxylate polyimide have a good enhancement effect on the performance of the ink film at the same time, and the tensile properties and hardness of the ink film are significantly improved, and the film mass loss △m and brightness change △L decrease to a large extent, and the wear resistance and scratch resistance are improved. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1

[0020] (1) In a flask equipped with a reflux tube, 150 mL of acetonitrile, 40 mmol of 4,4'-dinitrodiphenylamine (CAS No. 1821-27-8), 52 mmol of bromoacetic acid, and 56 mmol of potassium carbonate were added, heated to 80°C, reacted for 6 hours, filtered, and the filtrate was heated and concentrated. After the precipitate was precipitated, it was cooled in an ice water bath and recrystallized. Then, the recrystallized product was added to water, 6.8 g of reduced iron powder and 3.5 mL of 37% concentrated hydrochloric acid were added, heated to 95°C, reacted for 10 hours, and sodium carbonate was added for neutralization. After filtering, the filtrate was heated and concentrated. After the precipitate was precipitated, it was cooled in an ice water bath and recrystallized to obtain 4,4'-diaminodiphenylamine acetic acid.

[0021] (2) Add 120 mL of N,N-dimethylacetamide, 70 mmol of 4,4'-diaminodiphenylamine acetic acid, 30 mmol of 1,8-diamino-3,6-dioxaoctane (CAS No. 929-59-9), and 100 mmol of 4,4'-biphenyl ether dianhydride (CAS No. 823-59-2) into a flask, and react at 25° C. for 12 h. Then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction, successively at 100° C. for 1 h, 180° C. for 1.5 h, 200° C. for 1.5 h, and 250° C. for 1 h to obtain carboxyl polyimide.

[0022] (3) Add 300 mL of water and 20 g of carboxyl polyimide into a flask, add sodium hydroxide to adjust the pH of the solution to 12, stir, dry to remove water, and wash with ethanol to obtain a water-soluble sodium carboxylate polyimide.

[0023] (4) Add 800 g of water and 1 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, then add 5 g of water-soluble sodium carboxylate polyimide, stir and modify the surface at 50 ° C for 4 h, then add 770 g of water-based polyurethane, 220 g of phthalocyanine blue slurry, 5 g of defoaming agent Dow Corning AFE-1247, 12 g of leveling agent Xianchuang MFP-L, and 5 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0024] Example 2

[0025] (1) Add 200 mL of acetonitrile, 40 mmol of 4,4'-dinitrodiphenylamine, 40 mmol of bromoacetic acid, and 80 mmol of potassium carbonate to a flask equipped with a reflux tube, heat to 70°C, react for 8 hours, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, then add the recrystallized product to water, add 6.2 g of reduced iron powder and 4 mL of 37% concentrated hydrochloric acid, heat to 95°C, react for 10 hours, add sodium carbonate for neutralization, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, and obtain 4,4'-diaminodiphenylamine acetic acid.

[0026] (2) Add 120 mL of N,N-dimethylacetamide, 80 mmol of 4,4'-diaminodiphenylamine acetic acid, 20 mmol of 1,8-diamino-3,6-dioxaoctane, and 100 mmol of 4,4'-biphenyl ether dianhydride into a flask, and react at 30°C for 8 h. Then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction, successively at 100°C for 1 h, 180°C for 1.5 h, 200°C for 1.5 h, and 250°C for 1 h to obtain carboxyl polyimide.

[0027] (3) 400 mL of water and 20 g of carboxyl polyimide were added to a flask, and sodium hydroxide was added to adjust the pH of the solution to 10. After stirring, the solution was dried to remove water, and washed with ethanol to obtain a water-soluble sodium carboxylate polyimide.

[0028] (4) Add 800 g of water and 2 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, then add 10 g of water-soluble sodium carboxylate polyimide, stir and modify the surface at 70° C. for 2 h, then add 740 g of water-based polyurethane, 200 g of phthalocyanine blue slurry, 10 g of defoamer Dow Corning AFE-1247, 6 g of leveling agent Centron MFP-L, and 7 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0029] Example 3

[0030] (1) Add 200 mL of acetonitrile, 40 mmol of 4,4'-dinitrodiphenylamine, 46 mmol of bromoacetic acid, and 56 mmol of potassium carbonate to a flask equipped with a reflux tube, heat to 80°C, react for 5 h, filter, heat and concentrate the filtrate, cool in an ice-water bath after precipitation, recrystallize, then add the recrystallized product to water, add 8.5 g of reduced iron powder and 3.5 mL of 37% concentrated hydrochloric acid, heat to 100°C, react for 6 h, add sodium carbonate for neutralization, filter, heat and concentrate the filtrate, cool in an ice-water bath after precipitation, recrystallize, and obtain 4,4'-diaminodiphenylamine acetic acid.

[0031] (2) Add 120 mL of N,N-dimethylacetamide, 90 mmol of 4,4'-diaminodiphenylamine acetic acid, 10 mmol of 1,8-diamino-3,6-dioxaoctane, and 100 mmol of 4,4'-biphenyl ether dianhydride into a flask, and react at 20°C for 12 h. Then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction, successively at 100°C for 1 h, 180°C for 1.5 h, 200°C for 1.5 h, and 250°C for 1 h to obtain carboxyl polyimide.

[0032] (3) 400 mL of water and 20 g of carboxyl polyimide were added to a flask, and sodium hydroxide was added to adjust the pH of the solution to 11. After stirring, the solution was dried to remove water, and washed with ethanol to obtain a water-soluble sodium carboxylate polyimide.

[0033] (4) Add 1000 g of water and 4 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, then add 20 g of water-soluble sodium carboxylate polyimide, stir and modify the surface at 50 ° C for 4 h, then add 740 g of water-based polyurethane, 270 g of phthalocyanine blue slurry, 5 g of defoaming agent Dow Corning AFE-1247, 8 g of leveling agent Xianchuang MFP-L, and 4 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0034] Example 4

[0035] (1) Add 150 mL of acetonitrile, 40 mmol of 4,4'-dinitrodiphenylamine, 40 mmol of bromoacetic acid, and 56 mmol of potassium carbonate to a flask equipped with a reflux tube, heat to 70°C, react for 8 hours, filter, heat and concentrate the filtrate, cool in an ice-water bath after precipitation, recrystallize, then add the recrystallized product to water, add 6.4 g of reduced iron powder and 3.8 mL of 37% concentrated hydrochloric acid, heat to 95°C, react for 10 hours, add sodium carbonate for neutralization, filter, heat and concentrate the filtrate, cool in an ice-water bath after precipitation, recrystallize, and obtain 4,4'-diaminodiphenylamine acetic acid.

[0036] (2) Add 120 mL of N,N-dimethylacetamide, 70 mmol of 4,4'-diaminodiphenylamine acetic acid, 30 mmol of 1,8-diamino-3,6-dioxaoctane, and 100 mmol of 4,4'-biphenyl ether dianhydride into a flask, and react at 25°C for 12 h. Then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction, successively at 100°C for 1 h, 180°C for 1.5 h, 200°C for 1.5 h, and 250°C for 1 h to obtain carboxyl polyimide.

[0037] (3) Add 300 mL of water and 20 g of carboxyl polyimide into a flask, add sodium hydroxide to adjust the pH of the solution to 10, stir, dry to remove water, and wash with ethanol to obtain a water-soluble sodium carboxylate polyimide.

[0038] (4) Add 1000 g of water and 4 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, then add 30 g of water-soluble sodium carboxylate polyimide, stir and modify the surface at 60 ° C for 4 h, then add 700 g of water-based polyurethane, 270 g of phthalocyanine blue slurry, 8 g of defoaming agent Dow Corning AFE-1247, 12 g of leveling agent Xianchuang MFP-L, and 4 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0039] Comparative Example 1

[0040] (1) Add 800 g of water, 770 g of water-based polyurethane, 220 g of phthalocyanine blue slurry, 5 g of defoamer Dow Corning AFE-1247, 12 g of leveling agent Centron MFP-L, and 5 g of thickener hydroxyethyl cellulose into a container, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0041] Comparative Example 2

[0042] (1) Add 800 g of water and 1 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, add 770 g of water-based polyurethane, 220 g of phthalocyanine blue slurry, 5 g of defoamer Dow Corning AFE-1247, 12 g of leveling agent Centron MFP-L, and 5 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0043] Comparative Example 3

[0044] (1) Prepare water-soluble sodium carboxylate polyimide according to the method of Example 1.

[0045] (2) Add 800 g of water and 5 g of water-soluble sodium carboxylate polyimide into a container, stir and add 770 g of water-based polyurethane, 220 g of phthalocyanine blue slurry, 5 g of defoamer Dow Corning AFE-1247, 12 g of leveling agent Centron MFP-L, and 5 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0046] Comparative Example 4

[0047] (1) Add 120 mL of N,N-dimethylacetamide, 70 mmol of 4,4'-diaminodiphenylmethane, 30 mmol of 1,8-diamino-3,6-dioxaoctane, and 100 mmol of 4,4'-biphenyl ether dianhydride into a flask, and react at 25°C for 12 h. Then pour the solution onto a clean glass plate and place it in a heating box for thermal imide reaction, successively at 100°C for 1 h, 180°C for 1.5 h, 200°C for 1.5 h, and 250°C for 1 h to obtain polyimide.

[0048] (2) Add 800 g of water and 1 g of nano zinc oxide (average particle size 40 nm) into a container, stir and disperse, then add 5 g of polyimide, stir and modify the surface at 50 ° C for 4 h, then add 770 g of water-based polyurethane, 220 g of phthalocyanine blue slurry, 5 g of defoamer Dow Corning AFE-1247, 12 g of leveling agent Centron MFP-L, and 5 g of thickener hydroxyethyl cellulose, and shear and disperse in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink.

[0049] The wear-resistant and scratch-resistant water-based ink is poured into the mold and dried and cured at 70°C to form a paint film.

[0050] Refer to GB / T 6739-2022 for the hardness of the paint film and GB / T 1040.1-2018 for the tensile properties.

[0051] The wear resistance was tested according to the method of GB / T 1768-2006. The paint film wear tester was used for testing, with a load of 1kg and a turntable speed of 11m / s. The number of wears was 8000 times. The mass loss △m before and after wear was calculated. The smaller △m is, the better the wear resistance is.

[0052] The scratch resistance was tested with reference to the method of GMW14688. A five-finger scratch abrasion tester was used to perform a checkered scratch test with a force of 10N, and a colorimeter was used to test the brightness change △L value at the scratched part. The smaller the △L value, the better the scratch resistance.

[0053] Table 1

[0054]

[0055] Compared with Comparative Example 1, the addition of nano zinc oxide to the polyurethane ink of Comparative Example 2 improves the hardness and tensile strength of the ink film to a certain extent, and the mass loss △m and brightness change △L values ​​are reduced, and the mechanical properties, wear resistance and scratch resistance are improved. However, nano zinc oxide is prone to agglomeration, has poor compatibility with polyurethane, poor dispersibility, and the improvement of the hardness and tensile strength of the ink film is low, and the mass loss △m and brightness change △L are reduced to a small extent.

[0056] Compared with Comparative Example 1, Comparative Example 3 adds water-soluble sodium carboxylate polyimide. Polyimide itself has excellent mechanical strength, wear resistance and other properties, and it has good water solubility and can be well dissolved in water-based polyurethane ink, which is beneficial to improve the hardness, tensile strength and other mechanical properties of the ink film. And the film mass loss △m and brightness change △L are reduced, and the wear resistance and scratch resistance are improved. However, without the addition of nano zinc oxide, the mechanical properties and wear resistance and scratch resistance of the paint film are lower than those of the embodiments.

[0057] Nano zinc oxide and water-soluble sodium carboxylate polyimide are added to the polyurethane ink of Examples 1-4. The side chains of the polyimide contain a large number of sodium carboxylate groups, which can interact with the surface of the nano zinc oxide, thereby realizing the surface coating modification of the nano zinc oxide, which is beneficial to improving the dispersibility of the nano zinc oxide and reducing agglomeration, so that it can be evenly dispersed in the aqueous polyurethane ink. The evenly dispersed nano zinc oxide and water-soluble sodium carboxylate polyimide also have a great enhancing effect on the performance of the ink film. The tensile properties and hardness of the ink film are significantly improved, and the film mass loss △m and brightness change △L decrease significantly, and the wear resistance and scratch resistance are very good.

[0058] Comparative Example 4 utilizes 4,4'-diaminodiphenylmethane to react with 1,8-diamino-3,6-dioxaoctane and 4,4'-biphenyl ether dianhydride. The obtained polyimide does not contain hydrophilic sodium carboxylate groups, is not water-soluble, has poor compatibility with aqueous polyurethane ink, and does not contain sodium carboxylate groups. It cannot interact with the surface of nano zinc oxide and cannot play a role in surface modification. The dispersibility of nano zinc oxide is not improved, resulting in the tensile properties and hardness of the paint film being lower than those of the embodiments, the mass loss △m and the brightness change △L being higher than those of the embodiments, and the mechanical properties and wear and scratch resistance being poor.

Claims

1. A method for preparing a wear-resistant and scratch-resistant water-based ink, characterized in that: The wear-resistant and scratch-resistant water-based ink comprises 70-77 parts by weight of water-based polyurethane, 0.5-3 parts by weight of water-soluble sodium carboxylate polyimide, 1-4 parts by weight of nano zinc oxide, 20-27 parts by weight of color paste, 0.5-1 parts by weight of defoamer, 0.6-1.2 parts by weight of leveling agent, and 0.4-0.7 parts by weight of thickener; The preparation method comprises: adding water and nano zinc oxide into a container, stirring and dispersing, then adding water-soluble sodium carboxylate polyimide, stirring and performing surface modification, then adding water-based polyurethane, color paste, defoamer, leveling agent, thickener, shearing and dispersing in a shear emulsifier to obtain a wear-resistant and scratch-resistant water-based ink; The preparation method of the water-soluble sodium carboxylate polyimide is: (1) Add acetonitrile, 4,4'-dinitrodiphenylamine, bromoacetic acid, and potassium carbonate to a flask equipped with a condenser reflux tube, heat to 70-80°C, react for 5-8h, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, then add the recrystallized product to water, add reduced iron powder and concentrated hydrochloric acid, heat to 95-100°C, react for 6-10h, add sodium carbonate for neutralization, filter, heat and concentrate the filtrate, cool in an ice water bath after precipitation, recrystallize, and obtain 4,4'-diaminodiphenylamine acetic acid; (2) adding N,N-dimethylacetamide, 4,4'-diaminodiphenylamine acetic acid, 1,8-diamino-3,6-dioxaoctane, and 4,4'-biphenyl ether dianhydride into a flask to react, and then pouring the solution onto a clean glass plate, placing the solution in a heating box to perform a thermal imidization reaction, thereby obtaining a carboxyl polyimide; (3) Add water, carboxyl polyimide and sodium hydroxide into a flask, stir and dry to remove water, and wash with ethanol to obtain water-soluble sodium carboxylate polyimide.

2. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: The surface modification is performed at a temperature of 50-70° C. for 2-4 hours.

3. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: The molar ratio of 4,4'-dinitrodiphenylamine, bromoacetic acid and potassium carbonate in (1) is 1:(1-1.3):(1.4-2).

4. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: The molar ratio of 4,4'-diaminodiphenylamine acetic acid, 1,8-diamino-3,6-dioxaoctane and 4,4'-biphenyl ether dianhydride in (2) is (0.7-0.9):(0.1-0.3):

1.

5. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: The reaction temperature in (2) is 20-30°C and the reaction time is 8-12h.

6. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: The thermal imidization reaction in (2) is carried out at 100°C for 1 h, 180°C for 1.5 h, 200°C for 1.5 h, and 250°C for 1 h.

7. The method for preparing the wear-resistant and scratch-resistant water-based ink according to claim 1, characterized in that: In the step (3), sodium hydroxide is added to adjust the pH of the solution to 10-12.

Citation Information

Patent Citations

  • Superhard composite material containing diamond and graphene and preparation method

    CN117924701A

  • Wear-resistant coating containing modified aluminum oxide and preparation method of wear-resistant coating

    CN118344786A

Cited By

  • Sunproof and scratch-resistant gravure code spraying ink and preparation method thereof

    CN122356879A